2013
DOI: 10.3892/ol.2013.1448
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-199a is able to reverse cisplatin resistance in human ovarian cancer cells through the inhibition of mammalian target of rapamycin

Abstract: microRNAs (miRNAs/miRs) may have a crucial function in tumor metastasis through the regulation of a plethora of signaling pathways. Increasing evidence has shown that miR-199a is important in regulating the tumor metastasis of ovarian cancer, although the precise biological function of miR-199a is unclear at present. In the current study, it was observed that the expression levels of miR-199a were higher in OV2008 cells compared with C13* cells. However, lower levels of mammalian target of rapamycin (mTOR) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 18 publications
0
44
0
Order By: Relevance
“…A). Recent studies demonstrated that overexpression of miR‐199a/b‐3p suppressed proliferation, multidrug resistance, and migration in cancer cells with miR‐199a/b‐3p down‐regulated, such as in hepatocellular carcinoma , ovarian cancer , renal cell carcinoma , osteosarcoma , papillary thyroid carcinoma , and endometrioid adenocarcinoma . All of these phenomena demonstrated whether the decreased expression level of miR‐199a/b‐3p was associated with aggression of breast cancer.…”
Section: Discussionmentioning
confidence: 97%
“…A). Recent studies demonstrated that overexpression of miR‐199a/b‐3p suppressed proliferation, multidrug resistance, and migration in cancer cells with miR‐199a/b‐3p down‐regulated, such as in hepatocellular carcinoma , ovarian cancer , renal cell carcinoma , osteosarcoma , papillary thyroid carcinoma , and endometrioid adenocarcinoma . All of these phenomena demonstrated whether the decreased expression level of miR‐199a/b‐3p was associated with aggression of breast cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Cao and cols. (2014) concluded that patients with high expression of miR-200a, miR-200b, and mi-R200c present shorter overall survival than the corresponding controls (all p < 0.001) [21]. Moreover, Pal and cols.…”
Section: Mirnas As Chemotherapy Response Predictorsmentioning
confidence: 95%
“…Inhibition of invasion and metastasis [75] miR-888 Up E-cadherin Promotion of EMT [76] let-7 Down HRAS, HMGA2 Inhibition of self-renewal [77] miR-7 Down SETDB1 Inhibition of invasion and metastasis [78] miR-200c Down BMI-1, SUZ12 Inhibition of self-renewal [79] Colorectal cancer miR-21 Up TGFBR Modulation of Wnt signaling [80] miR-140 Up HDAC4, CXCL2 Chemosensitivity [81,82] miR-215 Up DTL Chemosensitivity [83] miR-34 Down NOTCH1 Suppression of asymmetric cell division [84] miR-93 Down HDAC8, TLE4 Inhibition of proliferation [85] miR-328 Down ABCG2 Inhibition of chemoresistance [86] miR-451 Down MIF, COX-2 Inhibition of self-renewal and tumorigenicity [87] miR-451 Down ABCB1 Inhibition of chemoresistance [87] Ovarian cancer miR-214 Up P53/NANOG Promotion of self-renewal [88] miR-199a Down CD44 Inhibition of proliferation and invasion [89] miR-199a Down mTOR Induction of chemoresistance of CD133+ cells [90] miR-200a Down ZEB2 Inhibition of migration and invasion [91] Prostate cancer miR-34 Down CD44…”
Section: Breast Cancermentioning
confidence: 99%
“…The inhibition of CD44 by miR-199a reduces expression of the multidrug resistance gene ABCG2 and thereby increases the chemosensitivity of ovarian CSCs [89]. In addition, miR-199a is also implicated in cisplatin resistance because inhibition of miR-199a increases mammalian target of rapamycin expression and decreases cisplatin-induced apoptosis in vitro [90].…”
Section: Ovarian Cancermentioning
confidence: 99%